Respuesta :
Answer:
The answer is y= −6
Step-by-step explanation:
Let's solve your equation step-by-step.
10−5y=2(14−y)
Step 1: Simplify both sides of the equation.
10−5y=2(14−y)
10+−5y=(2)(14)+(2)(−y)(Distribute)
10+−5y=28+−2y
−5y+10=−2y+28
Step 2: Add 2y to both sides.
−5y+10+2y=−2y+28+2y
−3y+10=28
Step 3: Subtract 10 from both sides.
−3y+10−10=28−10
−3y=18
Step 4: Divide both sides by -3.
−3y/−3=18/−3
y=−6
Answer:
y=−6
Answer:
y= -6
Step-by-step explanation:
10-5y=2(14-y)
10-5y=28-2y
10-5y+2y=28
-3y=28-10
-3y=18
y= -6